A Case of Listeria Monocytogenes Brain Abscess with a Clinical Presentation Mimicking Stroke - Ya-Chun Chu; Nai-Ching Chen; Chien-Liang Chen (Acta Neurologica Taiwanica)
Purpose: Kidney transplant recipients are at a high risk of both stroke and infection. We report this case to inform readers of the possibility of the occurrence of Listeria monocytogenes brain abscess despite treatment with low dose trimethoprim–sulfamethoxazole (TMP/SMX). Case Report: A 62-year-old man presented to our hospital with right facial palsy, left arm and leg weakness, and mild fever; he was diagnosed with a stroke in the emergency room. The patient had a history of cadaveric renal transplantation 2 years prior, for which he was prescribed tacrolimus- based immunosuppressive drugs. Multiple myeloma was diagnosed 18 months after renal transplant. He was treated with bortezomib and steroids for the multiple myeloma, and low-dose TMP/SMX for pneumocystis prophylaxis. A listeria brain abscess was diagnosed based on a comprehensive medical history, magnetic resonance images, positive blood culture, and brain biopsy. He underwent ampicillin therapy and achieved full recovery after a 3-month follow-up period. Conclusion: Physicians should monitor unusual stroke symptoms and consider Listeria brain abscess as a differential diagnosis. This case suggests that listeria brain abscesses can potentially cause temporary neurological deficits akin to a stroke, despite TMP/SMX prophylaxis, but these symptoms resolve without necessitating surgical intervention.